Out of sight but not out of mind: Size fractionation of plastics bioaccumulated by field deployed oysters - Ribeiro, Francisca; Okoffo, Elvis D.; O’Brien, Jake W.; O’Brien, Stacey; Harris, Jonathan M.; Samanipour, Saer; Kaserzon, Sarit; Mueller, Jochen F.; Galloway, Tamara; Thomas, Kevin V. (Journal of hazardous materials letters, 2021)
[Display omitted] •Quantification of the nano-sized fraction (< 1 μm) of plastic in bivalves is lacking.•Most of the plastic found in field deployed oysters was 1−22 μm and < 1 μm in size.•An important portion of microplastics is missed in most studies with bivalves. Microplastics contamination has been widely reported in filter feeders yet the < 1 μm size fraction has been largely ignored. In attempt to characterize this sub 1 μm size fraction and better understand the size distribution of microplastics contamination in filter feeders, field deployed oysters were characterised using a combination of size fractionation combined with pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS) as well as Fourier Transform-Infrared Spectroscopy (μFT-IR). Sequential filtration followed by Py-GC/MS identified the 1–22 μm fraction to contain the highest total plastic mass concentration (Ʃ31 mg/g), followed by the <1 μm fraction (Ʃ7.7 mg/g) and the >22 μm fraction (Ʃ0.1 mg/g). μFT-IR identified 0.2 particles/g tissue but was limited to particles >150 μm in size. Our results clearly show that an important size fraction of microplastics is being overlooked in almost all studies published to date that rely on FTIR for polymer identification.